2014
DOI: 10.1002/lary.24700
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of BST2 is associated with nodal metastasis and poorer prognosis in oral cavity cancer

Abstract: The findings in this study indicate that BST2 expression in OSCC tumors is an independent prognostic factor of patient survival and associated with tumor metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 39 publications
0
45
0
1
Order By: Relevance
“…17, 36, 37 BST2 is also reported to promote the growth and metastasis of breast cancer. 16, 38 Thus, BST2 may have a proto-oncogenic role and promotes cancer progression, 38 which is also consistant with our observation that knockdown of BST2 delayed the growth of NPC xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 36, 37 BST2 is also reported to promote the growth and metastasis of breast cancer. 16, 38 Thus, BST2 may have a proto-oncogenic role and promotes cancer progression, 38 which is also consistant with our observation that knockdown of BST2 delayed the growth of NPC xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11, 12 However, BST2 was first identified as a type II transmembrane glycoprotein expressed in bone marrow stromal cell lines and involved in pre-B-cell growth. 13 Accumulating evidence has shown that BST2 is also constitutively expressed on various other immune cells and malignant cells, 14, 15 such as breast cancer, 16 oral cavity cancer, 17 lung cancer, 18 B-cell chronic lymphocytic leukemia 19 and gastrointestinal cancer cells. 20 Nonetheless, BST2 is not elevated in all cancers.…”
mentioning
confidence: 99%
“…The spectrum of BST-2 expression in various cancers has been revealed using meta analyses studies of large tumor datasets [119]. In solid tumors, BST-2 expression is elevated in head and neck cancer [120], lung cancer [121], breast cancer [119,122,123], cervical cancer [124], myelomas [125,126], endometrial cancer [127], and glioblastoma [128]. In addition, data from proteinatlas.org reveal that BST-2 is overexpressed in colorectal cancer, ovarian cancer, thyroid cancer, and pancreatic cancer (http://www.proteinatlas.org/ ENSG00000130303-BST2/cancer).…”
Section: Bst-2/tetherin: Roles In Carcinogenesismentioning
confidence: 99%
“…Correlation studies using meta analyses of various tumor datasets showed that BST-2 levels are proportional to the aggressiveness of different cancers including breast [123,129], brain [128], and oral cavity cancers [120]. In vitro, overexpression of BST-2 in breast cancer cells enhanced cell migration, invasion, proliferation, and anchorage-independent growth [119,123,129] whereas BST-2 suppression results in reduced migration, invasion, anchorage-independent growth but not cell proliferation [45].…”
Section: Functional Roles Of Bst-2 In Cancermentioning
confidence: 99%
“…Although BST-2 is thought to antagonize the release of host cells from enveloped viruses, recent studies have shown that BST-2 is highly expressed in many types of tumors, such as head and neck tumors [7] , lung cancer [8], and breast cancer. [6,9] , cervical cancer [10] , myeloma, endometrial cancer [11] , etc., suggesting that BST-2 has a carcinogenic effect.…”
Section: Discussionmentioning
confidence: 99%